`PATTERN OF HISTOLOGIC VARIANTS OF AMELOBLASTOMA IN A SECONDARY HEALTH CARE FACILITY IN LAGOS STATE: A 5-YEAR RETROSPECTIVE STUDY. - Babalola Castano; Remilekun T OLUWAKUYIDE; Oluwafemi A ADESHINA; Funmi S Adenaike; Adeshina Ayodele; Oluwatosin Osobu; Kayode Adegbesan; Edward Faminu (Nigerian Dental Journal)
Background: Ameloblastoma is a benign epithelial odontogenic neoplasm which is common amongst the Yoruba ethinc group. The various histologic types have been elucidated.